2008
DOI: 10.1055/s-2007-1000416
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschalldiagnostik von Rippen- und Sternumfrakturen

Abstract: Rib fractures could be found about twice as often US than x-ray. There was no difference in the diagnosis of sternal fracture. Detection of fluids (local haematoma and pleural effusion) is better via US than by x-ray. Therapeutical consequences may follow a quick bed-side diagnosis by US in a patient who needs intensive care. Other aspects after detection of a rib fracture US apart from thoracic contusion are psychological effects for the patients (usually they can cope better with their pain), the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 0 publications
1
11
0
7
Order By: Relevance
“…If fractures are subtle and non-displaced, standard radiography may appear to show normal findings, despite the presence of clinical symptoms and increased uptake on bone scintigraphy [8,18]. Sonography has been known to detect rib fractures with greater accuracy than conventional radiography, but it is operator dependent and is not practical for use in an emergency setting [7,9,10]. Recently, CT has been considered to be the first choice modality for evaluation of trauma patients, including ones with thoracic trauma [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If fractures are subtle and non-displaced, standard radiography may appear to show normal findings, despite the presence of clinical symptoms and increased uptake on bone scintigraphy [8,18]. Sonography has been known to detect rib fractures with greater accuracy than conventional radiography, but it is operator dependent and is not practical for use in an emergency setting [7,9,10]. Recently, CT has been considered to be the first choice modality for evaluation of trauma patients, including ones with thoracic trauma [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that sonography reveals more fractures than radiography, but this modality depends on the operator's skill and is inaccessible to most emergency rooms [7,9,10]. Omert et al [11] reported that CT detected chest injuries in 39% of patients with an initial normal chest radiograph who were thought to have severe mechanism of injury.…”
mentioning
confidence: 99%
“…3), which appear as hypoechoic masses replacing the normal echogenicity of a rib and leading to the disruption of the cortical line [14]. Some evidence suggests that US may also be more sensitive than radiography in the detection of rib fractures [15], which appears as a breach or displacement of the rib cortex with or without a localized swelling or haematoma.…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%
“…Nevertheless, a recent meta-analysis concluded that bedside ultrasonography performed by clinicians had a higher sensitivity and similar specificity, when compared to chest radiography in the diagnosis of a pneumothorax [28]. A pneumothorax can be reliably diagnosed by means of the absence of normal lung sliding and lung pulse, exaggerated horizontal A-lines, the absence of B-lines and the presence of a lung point [1,2,4,15,28]. The ‘lung pulse’ refers to the subtle movements of the visceral pleura in relation to the parental pleura due to cardiac oscillations [4].…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%
“…An einigen Lokalisationen, z. B. an der Klavikula und den Rippen, ist die Sonografie sensitiver als die Röntgendiagnostik [15,19]. Ähnlich wie anhand von Röntgenaufnahmen finden sich gelegentlich Probleme bei komplexen Frakturen, gelenknahen Frakturen, insbesondere nicht dislozierten epiphysären Frakturen, und Frakturen der kleinen tubulären Knochen an Hand und Fuß [14].…”
unclassified